The 3rd Plasma Nanotechnologies and Bioapplications Workshop Scientific Program & Book of Abstracts - Šrámková, Petra; Kováčik, Dušan; Skácelová, Dana; Kelar, Jakub; Beigi, Pedram (Masaryk University Press, 2023)
Title in English: The 3rd Plasma Nanotechnologies and Bioapplications Workshop: Scientific Program & Book of Abstracts The Book of Abstracts contains contributions to the presentations of the third workshop organized by the Plasma Nanotechnology and Bioapplications Research Group at the Department of Plasma Physics and Technology, Faculty of Science, Masaryk University. The event, entitled "The 3rd Plasma Nanotechnologies and Bioapplications Workshop", was held at the Rustikal Hotel in Hustopeče from 9 to 12 October 2023. The workshop was attended by scientific teams from the Department of Plasma Physics and Technology of the Faculty of Science at Masaryk University, the Department of Experimental Physics and Division of Environmental Physics of the Faculty of Mathematics, Physics and Informatics at Comenius University in Bratislava, which are regular participants. However, this year's edition is also characterised by the abundant participation of international teams from Germany - HAWK University of Applied Sciences and Arts, University of Stuttgart; Slovenia - University of Ljubljana and Austria - University of Natural Resources and Life Sciences. During the workshop, contributions on the following topics were presented in the form of lectures: New developments and diagnostics of DBD, Plasma and glass processing, Plasma in contact with liquids & Plasma water purification, Plasma and bioapplications, Plasma reduced graphene oxide, and Plasma surface processes.